Performance Analysis of a Greenhouse Fan-Pad Cooling System: Gradients of Horizontal Temperature and Relative Humidity - Mehmet Ali Dayıoğlu; Hasan Hüseyin Silleli (Journal of Agricultural Sciences)
An experimental study was conducted to determine the performance parameters of system, as well as gradients of temperature and humidity along greenhouse when opening fan-ped cooling system. Measurements related with greenhouse environment were carried out by using seven sensors for different locations, as well as portable instruments. For this purpose, the five digital temperature and humidity sensors and two pyranometers were used during experiments. Among them, two were located outside greenhouse for external measurements. The rest one pyranometer above the crop canopy, four temperature and humidity sensors were mounted within the crop canopy along the greenhouse. Four sensors were placed according to positions defined between pad and fan. According to the experiment results, the non-uniform temperature changes, but approximately uniform humidity changes due to the crop transpiration were observed along greenhouse from pad panels to exhaust fans.When the cooling system closed, hourly mean temperature and relative humidity from pad to fan inside greenhouse changed between 30–33°C and 30–47%, respectively, at outside climate conditions of 32°C and 25%. After providing stabile cooling by opening fan-pad system, hourly mean temperature and relative humidity along greenhouse from pad to fan ranged between 20 – 27°C, and 50 – 68%, respectively. The air temperature entering to greenhouse with air velocity of 0.8–0.9 ms-1 through pad was approximately 12–13ºC lower than the outside air temperature. The air temperature from pad to fan increased approximately by 7 ºC.The method of psychrometric calculations was employed to determine the cooling efficiency of fan-pad system. According to the calculation result, the average of air temperatures inside greenhouse was 24.5 ºC after achieving stable cooling for outside air temperature of 31.4 ºC. The hourly mean cooling effect and cooling efficiency calculated for fan-pad system were determined to be 6.96ºC and 76.8%, respectively.